To What Extent Should National Security Interests Override Privacy in a Post 9/11 World - Laberge, Cynthia (Victoria University of Wellington Law Review, 2009)
September 11, 2001, and the subsequent bombings in Madrid and London in 2004 and 2005, made it clear that no country was immune from terrorism. In the wake of those attacks, nations united to implement programmes to track terrorists and prevent future attacks. Leading the worldwide effort was the US with its programmes to screen travellers through airline reservation systems, mine data of unsuspecting telecommunication company customers, and track and intercept banking communications. As these programmes came to light (often through leaks to the press), many were criticised both in the US and overseas as invading privacy and violating laws. Some of these programmes have been challenged in courts in the US and Europe, others have been scaled back, restructured, or discontinued. The question is: Do these programmes actually work and, even if they do, are they worth the cost to privacy interests?